The Role Of African Risk Capacity In Mitigating The Food Crisis Due To Climate Change In Mali In 2021-2022 - Wicaksono, Adhitya Sandy; Candra, Rudi (Mediasi Journal of International Relations, 2023)
This study aims to explain the role of the African Risk Capacity (ARC) organization in tackling the food crisis due to climate change in Mali in 2021-2022. This study used a descriptive qualitative method, with the research object describing the role of the ARC organization in tackling the food crisis due to disasters related to climate change in the country of Mali and using a literature study as a data collection technique. From this study, the authors found that ARC climate risk insurance has an impact on reducing hunger and poverty in Mali by 2021 by providing financial support for emergency response and disaster risk reduction initiatives. ARC also assists with disaster management program planning and participates in carrying out supervision when the program is implemented. ARC's efforts have proven to help ease the burden on local governments in responding to climate hazards and reduce the impact of climate-related disasters on the most vulnerable populations and gradually increase their welfare.